Eulerian Graph in STEM Learning Approach : Local Instruction Theory for Prospective Mathematics Teacher - Ria Deswita; Febria Ningsih (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to design a LIT of Eulerian graphs based on the STEM learning approach. By combining LIT with the STEM approach, teaching Eulerian graph material can be done in a more applicable and easily understood way by prospective mathematics teacher students. This study is a design research study with three stages, preliminary design, design experiment, and retrospective analysis. The trial was conducted on fourth-semester prospective mathematics teacher students of the Mathematics Education Department, Faculty of Education and Teacher Training, IAIN Kerinci. The instruments used were validation sheets and student response questionnaires. The analysis was carried out quantitatively and qualitatively. Based on data analysis, it was found that 1) The stages carried out to obtain a LIT of Eulerian graphs based on the STEM learning approach consisted of preliminary design (analyzing subjects, setting objectives, literature review, compiling HLT, and expert validation), design experiments (pilot experiments and teaching experiments), and retrospective analysis. 2) Local instruction theory of Eulerian graphs based on the STEM learning approach is practically applied in learning with a practicality percentage of 88% which is categorized as very practical. The application of LIT in learning Eulerian Graph with the STEM approach shows positive results in improving the mathematical understanding of prospective mathematics teacher students.